Identification of The Potential for The Independence of MSMEs in The Muara Tami District of The Indonesia-PNG Cross-Border Border - Apriani, Anita; Arisandi DN, Dani; Asabhi, Muhammad Malik; Giban, Darpin (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
The research aims to identify the potential independence of the MSME actors in villages in Muara Tami District, on the border of Indonesia and Papua New Guinea (PNG). Using a qualitative descriptive method with SWOT analysis, we seek to find strengths and opportunities as an overview of the potential independence of the MSME actors. The research focuses on indigenous Papuans (OAP) who operate the MSME business in the Muara Tami District. The data collection technique uses observation, interview, and documentation study. Three research stages were employed: exploration, interpretation, and contextualization. The results show that the MSME actors have the potential to create independence in developing their business activities by utilizing their strengths and opportunities as well as overcoming the weaknesses and threats faced. In the SWOT analysis, MSME actors are in the first quadrant, indicating the strengths and opportunities that can be used to develop MSME activities in the region.